The Strategy and Political Resources in the Changing of Spatial Policy - Aslinda, Aslinda; Ibrahim, Muhammad Akmal (UI Scholars Hub, 2016)
The spatial planning policy as included in the Local Regulation No. 6/2006 on the spatial planning of Makassar in 2005-2015 has changed from the original blueprint. The policy changing occurred on decisions or programs, but not on institutional regulations. The decisions or programs on spatial planning that were different from the original policy were visible on the licensing decisions in the Development Region I and Development Region III. The purpose of this research was to analyze the changing of the spatial planning policy that was resulted from the behavior of the advocacy coalition who competed with each other in the utilization of strategy and political resources, which was assumed to be affecting the policy output. The study results indicated that the changing of the spatial planning policy in Makassar was resulted from the competition between the major advocacy coalition and the minor advocacy coalition in influencing the policy. The Major Advocacy Coalition used the combination of strategy and political resources more in comparison to the minor advocacy coalition. The utilization of strategy from each advocacy coalitions was effective in several cases but ineffective in other cases. The difference in the effectiveness of the utilization of strategy was on the interests in each cases. In the projects that were based on public interests, the Major Coalition was more systematic in advocating the policy core beliefs, but in other projects that were based on private interests, the Major Coalition was likely to withdraw.